Caring and Connectivity: A Framework for Active Caring in the Music Classroom. (June 2020) - Watts, Sarah; Eldreth, James; Grant, Timothy; Renne, Julie
In an age where caring for others may seem like a relic of a bygone era, we all must be reminded of the importance of active caring in the classroom and beyond. This article explores the work of Nel Noddings, an educational scholar at the forefront of caring research, and her four dimensions for bringing active caring into the classroom. Modeling, dialogue, practice, and confirmation provide teachers with concrete starting points for reflecting on the ways in which they cultivate caring in their music classrooms and how they develop caring relationships with students that reflect the ways they need and want to be cared for. Music educators often work with the same students over the course of many years—it is to our advantage to use this time to teach caring and teach with care.